An Overview of the Network of Meanings of the Prepositions “Ala” in the Quran With the Cognitive Approach - Maryam Tavakolnia; Valiollah Hasoumi (آموزه‌های قرآنی, 2019)
The word “Ala” is one of the Arabic prepositions used in many cases in the Quran. This in the sense of its proto-scene encodes the concept of transcendence. But all the uses of this term in the Qur'an are not limited to this proto-scene meaning. It has entered into new semantic domains by being in different tissues and in various ways. The present paper uses a descriptive-analytical method and uses the principles of cognitive semantics to examine the applications of this statement in the Qur'an in order to provide a meaningful analysis of its meanings. Therefore, based on the principles of cognitive semantics, the proto-scene meaning of the prepositions “Ala” was first identified, then the quality of the extension of this proto-scene meaning was examined. According to the studies, this preposition with its central meaning, through metaphor and schematics, has entered into new conceptual areas and created a network of different meanings. In shaping these meanings, factor and tissue changes play an important role.